1995
DOI: 10.1002/ijc.2910610503
|View full text |Cite
|
Sign up to set email alerts
|

International renal‐cell cancer study. IV. Occupation

Abstract: The relationship between renal-cell cancer (RCC) and occupation was investigated in an international multicenter population-based case-control study. Study centers in Australia, Denmark, Germany, Sweden and the United States interviewed 1732 incident RCC cases and 2309 controls. Significant associations were found with employment in the blast-furnace or the coke-oven industry [relative risk (RR), 1.7; 95% confidence interval (CI), 1.1-2.7], the iron and steel industry (RR, 1.6; 95% CI, 1.2-2.2) and exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
2
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(99 citation statements)
references
References 27 publications
(33 reference statements)
2
92
2
3
Order By: Relevance
“…In addition to several reviews human evidence evidence (13). (115) and Swaen (116) about the design of their study (10), calculate the combined OR among six case-control studies (60)(61)(62)(63)(64)83) McLaughlin and Blot (116) subsequently review the epidemiology of TCE and kidney cancer in seven cohort studies (10,18,19,24,30,31,104) and six case-control studies (57,(60)(61)(62)83,84) In their discussion, they fail to distinguish results either between men and women or incidence and mortality, and argue that none of the cohort studies except "the methodologically questionable" Henschler et al. study (10) The newest data on kidney cancer suggest different interpretations, although Weiss (6) and McLaughlin and Blot (117) caution the reader on the interpretation of these results because the Tier I cohort studies they had available showed, at best, a weak response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to several reviews human evidence evidence (13). (115) and Swaen (116) about the design of their study (10), calculate the combined OR among six case-control studies (60)(61)(62)(63)(64)83) McLaughlin and Blot (116) subsequently review the epidemiology of TCE and kidney cancer in seven cohort studies (10,18,19,24,30,31,104) and six case-control studies (57,(60)(61)(62)83,84) In their discussion, they fail to distinguish results either between men and women or incidence and mortality, and argue that none of the cohort studies except "the methodologically questionable" Henschler et al. study (10) The newest data on kidney cancer suggest different interpretations, although Weiss (6) and McLaughlin and Blot (117) caution the reader on the interpretation of these results because the Tier I cohort studies they had available showed, at best, a weak response.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these studies, there are concerns about selection bias, blinding of investigators or interviewers, and particularly exposure characterization. Some studies use job titles to infer exposure (60,63,67), one compares dry cleaning workers to laundry workers (59), others assess risk to subjects exposed to general classes of solvents (57,63), and still other studies ask about exposure to specific agents or used more sophisticated exposure characterizations ( Elevated odds ratios for kidney cancer are found for four different exposure classifications: degreasing agents (including TCE ) (60,61,66), solvents (61,63,65), the iron/ steel industry (likely including exposure to degreasing agents or solvents) (58,(62)(63)(64)(65), and dry cleaners/laundry workers (60,64,65). A few studies assesses TCE exposure specifically (66,68,84 (66), is hospitalbased using accident victims as controls.…”
Section: Community-based Studiesmentioning
confidence: 99%
“…Bunlardan bir tanesi asbest maruziyeti olup hastanın kendi ifade ettiği maruziyet ile BHK gelişme riskinin 1,4 kat arttığını bildirilmektedir. Bu risk kadmiyum maruziyetinde 2 kat, kuru temizlemede kullanılan çözeltilere maruziyette 1,4 kat, benzin ve diğer petrol ürünlerine maruziyette 1,6 kat artmaktadır (41). Daha sonra yapılan bir meta-analizde asbestin BHK gelişimindeki rolünün daha az önemli olabileceğini (42), bir başka meta-analizde de anlamlı ilişki bulunmadığı belirtilmiştir (43) Trichloroethylene (TCE) endüstriyel bir çözelti olup metal üzerindeki yağların temizlenmesinde kullanılır.…”
Section: Meslek Ile Ilişkili Faktörlerunclassified
“…An international population-based case-control study was carried out in Australia, Denmark, Germany, Sweden and the USA using a similar protocol in the participating centres (Mandel et al, 1995). Cases were patients with incident renal-cell carcinoma 189.0], histologically confirmed and diagnosed between 1989 and 1991.…”
Section: 22mentioning
confidence: 99%
“…Exclusion of women did not modify the result (odds ratio, 1.21; 95% CI, 0.43-3.45; based on seven exposed cases). Restriction to blue-collar workers increased the association (for men and women combined: odds ratio, 4.4; 95% CI, 0.4-43; for men only: odds ratio, 5.5; 95% CI, 0.5-58.9).An international population-based case-control study was carried out in Australia, Denmark, Germany, Sweden and the USA using a similar protocol in the participating centres (Mandel et al, 1995). Cases were patients with incident renal-cell carcinoma 189.0], histologically confirmed and diagnosed between 1989 and 1991.…”
mentioning
confidence: 99%